Influência da pozolanicidade na ativação alcalina - Leonardo Martins Costa (2020)
Geopolymers are low calcium alkali-activated materials. These materials are studiedas an alternative tocement in some civil construction applications. Many geopolymer precursors, such as metakaolin,also are pozzolanic or fillers materials incementitious composites. It suggests a possible correlation between pozzolanicity and geopolymerization. Then, this paper aims to analysethe influence of the pozzolanicity on the alkali activation of precursors constituted by metakaolin and different high silica materials. Metakaolin, silica fume, rice ash husk, amber soda-lime glass and quartz sand were analyzed by means BET specific surface, granulometric curves, and XRD/Rietveld refinement analysis. Thepozzolanic activity was evaluated by the Modified Chapelle test and termogravimetric analysis in cement pastes. Based on these results, geopolymers with or without a 15%replacement of metakaolin by rice ash husk and quartz sandwere synthetized.The alkaline activator was an admixture ofNaOH 8M and sodium silicate. Analysis of compressive strength, XRD, FTIR,and TEM were employedto evaluate the geopolymerization. The results indicate that metakaolin and silica fume have higher BET values and fixed lime contents in cement pastes. However, the rice husk ash had higher pozzolanicity by the Modified Chapelle test.The quartz sand wasnot pozzolanic material.This indicates thatthe pozzolanicityindex of materials in cement pastesincreased as a function of its BET specific surface. In the Modified Chapelle test,the agglomeration of thinparticlescould be underestimating thepozzolanicity index. Although, the differences of pozzolanicity among metakaolin, rice husk ash, and quartz sand had little influence on the compressive strength of geopolymers. The high reactivity of sodium silicate could mitigate the pozzolanicity effect of precursors materials. Besides, the filler effect of quartz and rice husk ash could contributetothe densification of geopolymers microstructure. The FTIR and XRD spectra showthe formation of new structures by alkali activation. Also, TEM images and electrondiffraction analysis indicates the formation of amorphous and particulate structures typical of N-A-S-H gel. So, it indicatesthat the structures formed by alkali activation are due to the geopolymerization of metakaolin and that the filler effect enhancedthe mechanical strength of geopolymers.